Sister Ship Binding Clause as a Reinforcement of Debt Repayment Legal Certainty on Ship Mortgage - Fani Martiawan Kumara Putra (Universitas Airlangga, 2020)
The field of marine transportation plays a role that is not less important than land transportation in terms of economic development in Indonesia. As a result of globalization, business activity continues to increase, whether it is business in the field of marine transportation or outside the field, it is certainly undeniable that the activity requires a very large funds, which funds can be obtained by one way is to apply for credit/loans. Large amount of loans will only be given with the imposition of collateral as a further process. The imposition of collateral for large amount of loans may designate the ship as its collateral object by utilizing the Mortgage security agency. However, when the ship is being vetted on a voyage across national borders, the impact is when its debts mature, then the execution of such ship will be difficult, caused by the inadequate legal rules in Indonesia, and not all countries ratify the ship’s arrest convention. This study aims to provide a solution in order to achieve legal certainty of Mortgaged object execution that being across national borders for a significant development of shipping business. This research is normative research. The result obtained is the need of a clause in the Mortgage security document concerning the binding of sister ship with equal value, as the collateral object backup, when the execution of ship loaded with Mortgage security is unable to be done since it is located outside the state border.